2007
DOI: 10.1021/la701741m
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Monolayer Formation on Aluminum-Doped Zinc Oxide Thin Films

Abstract: The optical and electronic properties of aluminum-doped zinc oxide (AZO) thin films on a glass substrate are investigated experimentally and theoretically. Optical studies with coupling in the Kretschmann configuration reveal an angle-dependent plasma frequency in the mid-IR for p-polarized radiation, suggestive of the detection of a Drude plasma frequency. These studies are complemented by oxygen depletion density functional theory studies for the calculation of the charge carrier concentration and plasma fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 71 publications
(139 reference statements)
3
20
0
Order By: Relevance
“…Reflectance FTIR spectroscopy revealed a sharp decrease in the optical reflectivity in the mid-IR of CTO suggestive of a surface plasmon resonance condition. The observed frequency dip in CTO at ∼ 3500 cm − 1 is comparable to the experimentally observed plasma frequencies of other metal oxide thin films such as ITO and AZO at ∼8500 cm − 1 [32,33], IrO 2 at ∼6500 cm − 1 [31], and RuO 2 at~4500 cm − 1 (unpublished data) using analogous reflectance FTIR spectroscopy. As shown in previous work on ITO [33], the deposition of an adlayer also affects the optical and electronic properties of the CTO thin film by changing both the position and slope of the plasma frequency.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Reflectance FTIR spectroscopy revealed a sharp decrease in the optical reflectivity in the mid-IR of CTO suggestive of a surface plasmon resonance condition. The observed frequency dip in CTO at ∼ 3500 cm − 1 is comparable to the experimentally observed plasma frequencies of other metal oxide thin films such as ITO and AZO at ∼8500 cm − 1 [32,33], IrO 2 at ∼6500 cm − 1 [31], and RuO 2 at~4500 cm − 1 (unpublished data) using analogous reflectance FTIR spectroscopy. As shown in previous work on ITO [33], the deposition of an adlayer also affects the optical and electronic properties of the CTO thin film by changing both the position and slope of the plasma frequency.…”
Section: Discussionsupporting
confidence: 81%
“…At an incident angle of 70°, the reflectance below 3500 cm − 1 is nearly 40% while above 3500 cm − 1 , the reflectance drops to approximately 15%. This observed change in reflectance is similar to observed changes in other conducting metal oxides (CMO) such as ITO, IrO 2 , and aluminum-doped zinc oxide (AZO) [14,[31][32][33]. A sharp change in the optical reflectivity such as this is indicative of the transition to the plasma resonance frequency, which is the resonant frequency for the conduction electrons in a Drude model.…”
Section: Resultssupporting
confidence: 74%
“…11 Rhodes et al focused the theoretical portion of their study on the zinc-sulfur bond and concluded partially on the basis of a calculated large Zn-S bond enthalpy that their C 16 and C 18 -thiolate monolayers on aluminum-doped ZnO were robust. 17 In all of these studies, the authors focused on the sulfur-zinc oxide interaction, neglecting the other side of the molecular anchoring group. In refs 11 and 12, the intensity of the S 2p core level was followed and used as the sole measure of the thiol coverage in temperature-dependent measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In our experimental setting described before, the focal spot are about 1590 µm 2 and the ZnO film has 2 µm thickness, thus the illuminated volume is about 3180 µm 3 and η was estimated to by 10 -5 in our experimental set up. The value of (a) is found from the measurements of P f at different values of I o , and by applying Equation (11), it was found to by about of 0.0142 cm 3 /GWatt 2 .…”
Section: R K Jamal Et Al 860mentioning
confidence: 99%
“…The ZnO nanostructures have many applications in gas sensors, UV detectors and solar cells [1][2][3]. This material has some additional advantages compared to other large band-gap semiconductors; for example, its large exciton binding energy (about 60 meV) which is three times the binding energies of ZnSe and GaN [4].…”
Section: Introductionmentioning
confidence: 99%